2016
DOI: 10.26719/2016.22.5.301
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of iodine deficiency disoriders among school children in Saudi Arabia: results of a national iodine nutrition study

Abstract: This study aimed at establishing updated data on iodine nutrition among schoolchildren in Saudi Arabia. A cross-sectional cluster survey among schoolchildren aged 8-10 years was conducted during February-April 2012. Children were clinically examined for goitre, urine and household salt samples were collected to estimate urinary iodine concenteration (UIC) and iodine content in salt. The overall goitre prevalence at the national level among 4 016 children was 4.2%. The prevalence was < 5% in all regions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…Nevertheless, only 70% of the Saudi households were using iodised salt, which did not reach the USI target of ≥ 90% coverage [27]. The present study is aligned with the prior national studies proclaiming iodine adequacy in the general Saudi population since the non-pregnant women were iodine sufficient [5,16,34]. However, the levels were at the lowest margin of adequacy, thus providing additional sustenance for the prior demands to ban noniodised salt in order to enhance iodine intake in KSA [27].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Nevertheless, only 70% of the Saudi households were using iodised salt, which did not reach the USI target of ≥ 90% coverage [27]. The present study is aligned with the prior national studies proclaiming iodine adequacy in the general Saudi population since the non-pregnant women were iodine sufficient [5,16,34]. However, the levels were at the lowest margin of adequacy, thus providing additional sustenance for the prior demands to ban noniodised salt in order to enhance iodine intake in KSA [27].…”
Section: Discussionsupporting
confidence: 79%
“…The IGN report (2019) has classified the general Saudi public as iodine sufficient based on the outcomes of a 2012 national SAC survey [5,16]. Others also showed an enhancement of SAC iodine status after the execution of USI in the Southwestern of KSA, a previously classified severe iodine deficient region [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Contrary to this, lower figures of IDD was reported in a study conducted in Saudi Arabia, (Al Dakheel, et al). 18 Abuye et al, in Ethiopia, reported 23% higher prevalence of Goiter among children of low income family than the family having higher income. 19 The higher goiter rate in low income category could be because of poor food security, including less meat and vegetable consumption, use of non-iodized salt, lack of medical attention.…”
Section: Discussionmentioning
confidence: 97%
“…About 90% of ingested iodine from diet and/or supplement is excreted by the kidney and, therefore, measuring urinary iodine concentration (UIC) is the recommended biochemical approach for assessing iodine status [13][14][15] However, compliance with the collection of 24-hour urine is low and spot urine analysis as well as estimating 24-hour urine iodine excretion (24-hr UIE) are alternative more convenient and accurate methods for measuring iodine intake [13][14][15]. Surveying school-age children (SAC) is also the currently accepted mean for evaluating iodine status within a population since they are easy to access, and it is believed they reflect the nutritional status of their families [16]. Yet again, the most recent report by the Iodine Global Network (IGN) in 2019 has indicated that 29 out of the 40 countries with data on iodine status among SAC and pregnant women have reported sufficiency in the former group, whereas deficiency was common during pregnancy [5].…”
Section: Introductionmentioning
confidence: 99%